Extent of depression among dialysis patients in Africa: a scoping review - Ngema, Siyanda A; Ramalepa, Tshiamo N (African Journal of Nephrology, 2025)
Background: The diagnosis of kidney failure has a significant impact on the quality of life of dialysis patients in various healthcare-related aspects, potentially leading to the development of depression and anxiety. Conversely, depression and the effects of dialysis adversely affect caregivers and families of dialysis patients. These patients experience depression for a variety of reasons, including the psychological effects of chronic illness, lifestyle constraints, and the physical difficulties of therapy. Research on the prevalence and effect of depression in dialysis patients in Africa is limited, highlighting the need for comprehensive studies to address them. This study synthesizes current evidence on depression among dialysis patients in Africa using a scoping review. Method: A systematic review of articles in PubMed, EMBASE, PsycINFO, African Journals Online (AJOL), and the Cochrane Library was conducted using keywords related to depression, dialysis, and renal disease in Africa, listing studies published between 2014 and 2024. A Microsoft spreadsheet was used to record the details of selected studies. Thirteen surveys met the criteria for final review, which followed the PRISMA-ScR guidelines, descriptive analysis and thematic analysis. Results: We found that the prevalence of depression in African dialysis patients ranged from 32.4% to 80%, depending on the country and study population. This evidence was categorised into four main themes: mental health and quality of life; socio-economic and treatment factors; self-management and psychosocial support; and geographic, cultural, and clinical implications. The limited number of peer-reviewed research papers identified is of concern, considering the topic’s significance and growing importance. Conclusion: Depression is prevalent among patients undergoing renal replacement therapies, such as haemodialysis and peritoneal dialysis. Regular assessments of depression are crucial for new dialysis patients to ensure early detection and optimal intervention. Further research is needed to improve the screening, diagnosis, and management of depression among dialysis patients in Africa.